New method and indicator for measuring women's empowerment through gamification - CGIAR Research Program on Rice (2019)
The new method and indicator are published in the Journal of Rural Studies and have been piloted in the Philippines and subsequently implemented through large-scale behavioral experiments in eastern India (Odisha and West Bengal), Bangladesh, the Philippines and Cambodia.